Extracellular matrix alterations in the Peyronie’s disease - Marcelo Silva Watanabe (Journal of Advanced Research, 2017)
Peyronie’s disease is characterized by fibrous plaque formation of the tunica albuginea, causing penile deformity and fertility problems. The aim of the present study was to investigate alterations in the extracellular matrix in Peyronie’s disease. The study used tissues collected by surgical procedure from individuals that presented a well-established disease, while control samples were obtained by biopsies of fresh cadavers. Immunohistochemistry analysis followed by digital quantification was performed to evaluate TGF-β, heparanases and metalloproteinases (MMPs). The profile of sulfated glycosaminoglycans, chondroitin sulfate and dermatan sulfate was determined by agarose gel electrophoresis, while hyaluronic acid quantification was obtained by an ELISA-like assay. The expression of mRNA was investigated for syndecan-1 proteoglycan (Syn-1), interleukine-6 (IL-6), hyaluronic acid synthases, and hyaluronidases. Pathologic features showed decreased apoptosis and blood vessel number in Peyronie’s tissues. TGF-β and IL-6 were significantly enhanced in Peyronie’s disease. There was an increased expression of heparanases, though no alteration was observed for MMPs. Hyaluronic acid as well as hyaluronic acid synthases, hyaluronidases, and dermatan sulfate were not changed, while the level of chondroitin sulfate was significantly (P = 0.008, Mann-Whitney test) increased in Peyronie’s samples. Heparanases and sulfated glycosaminoglycans seem to be involved in extracellular matrix alterations in Peyronie’s disease.